If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(6 + -4n) + -2n = -146 (6 * -6 + -4n * -6) + -2n = -146 (-36 + 24n) + -2n = -146 Combine like terms: 24n + -2n = 22n -36 + 22n = -146 Solving -36 + 22n = -146 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 22n = -146 + 36 Combine like terms: -36 + 36 = 0 0 + 22n = -146 + 36 22n = -146 + 36 Combine like terms: -146 + 36 = -110 22n = -110 Divide each side by '22'. n = -5 Simplifying n = -5
| 86+9x=89+6x | | 2/3-1/1 | | 5+3g=29 | | 5/12/7/24 | | -3(8x+2)-6=-108 | | 0.4x+11.4=x-6.9 | | 107+9x=109+8x | | 6(x+1.08)=5x | | -3x-y=-7 | | 5x-4y=-14 | | -xsquared+7x+11=0 | | 6(1+6x)=-54 | | 89+6x=93+4x | | 24x^5-20x^4+4x^3= | | 0=9-2(x/100) | | y/5+6=y/3+2 | | 10[7-4(7-5)]= | | x+y-3=2y | | C=5/9(14-32) | | 5(x+2)-2=-17 | | m/2-m=3 | | 3c^2(4c+5c^3)= | | 6x=1/6 | | 6-5(8-4)= | | 5(x+1)+x=17 | | 0=4x-36 | | -6/11m=-1/4 | | 0=2x-22 | | 0=6x-90 | | 4(2x-3)=-28 | | -1/5=x-7/9 | | 2f^2-288=0 |